THE IMPACT OF COMMUNICATION TECHNOLOGY ON THE QUALITY OF INTERPERSONAL COMMUNICATION IN DAILY LIFE - Tazkia Aulia Kamila (Journal of Learning on History and Social Sciences, 2024)
The development of technology today is very directly proportional to the survival of human beings in their level of needs and development. In recent decades, one of the technologies that has experienced significant advancements is Communication Technology. Communication is an integral part of human behavior, and almost all aspects of human life involve communication in various forms. Communication technology is changing the way people interact and has a number of significant impacts on the quality of communication. This journal examines how communication technology has an impact on the quality of interpersonal and professional communication and its implications for society